Evaluasi Stabilitas Formulasi Krim Ekstrak Propolis Geniotrigona thoracica - Paula Mariana Kustiawan; Deasy Nur Chairin Hanifa; Muhammad Alib Batistuta; Azzah Fatimah Zulfa (Journal Syifa Sciences and Clinical Research, 2022)
Methanolic extract of Geniotrigona thoracica propolis has been reported as strong antioxidant. This potential can be applied as cream product. This aims of this study is to evaluate the physical stability of the formulation of G. thoracica propolis cream which has antioxidant activity. The extract was obtained from propolis through the maceration method and then formulated into a cream dosage form. Detemination of the physical properties of cream product were included organoleptic test, homogeneity test, pH test, dispersibility test and adhesion test. The results of the stability evaluation of G. thoracica propolis cream showed a light brown color consistency, a weak characteristic odor and a soft semi-solid texture, homogeneous, pH 7, 6.5 cm spreadability and 260 seconds stickiness. The preparation of the G. thoracica propolis extract cream met the requirements of the physical tests performed. In addition, the G. thoracica propolis has good physical stability during storage.